ESTUDO DO COMPORTAMENTO DE ESTROGÊNIOS E DE SUAS INTERAÇÕES COM SUBSTÂNCIAS HÚMICAS - Sierpinski, Sheisa Fin Dantas (2015)
Organic micropollutants are substances that present even in small concentrations, are capable of triggering effects on systems where it is introduced, highlighting, among them the so-called endocrine disruptors (EDs). The EDs are substances that can interfere with the functions of the endocrine system, causing adverse effects to an organism or its offspring. Natural and synthetic sexual hormones are potent and EDs have been detected in aquatic environments on all continents, mainly due to the absence or deficiency in wastewater treatment processes. Humic substances (HS) are the main compounds able to interact with organic micropollutants such as hormones, interfering in the processes of bioavailability for the environment. Studies using HS as a complexing hormones have been carried out using the quantification method as chromatography. However, there are few studies of alternative methods for the quantification of estrogen hormones. The objective of this study was to validate and adapt a methodology to study estrone (E1), 17-estradiol (E2) and 17-ethinylestradiol (EE2) and study their interactions with humic substances employing molecular absorption spectroscopy Ultraviolet-Visible to quantify these hormones. This method is based on the diazotization of sulfanilamide with sodium nitrite, followed by coupling reaction with the hormone. Be established analytical curve for concentrations in the range from 10.0 to 28.0 μg mL-1 which was linear, adequate accuracy and precision. Despite the spectroscopic method is not selective, it presented results compatible with chromatography, which proves their suitability for the bench studies in this work. To perform a comparison between the methods employed to high performance liquid chromatography, using methanol and water as mobile phase and C-18 cartridge as stationary phase. For the study of interaction we used samples patterns of hormones in study and humic acid solution under constant agitation and samples taken within a maximum period of 48 hours. The reduction in the concentration of estrogen in the middle of the study, when in the presence of SH was detected since the beginning of the process. In all cases, we observed an increase in the removal of the hormone with increasing contact time. The reduction in the concentration of estrogen in the middle of the study, when in the presence of HSwas detected since the beginning of the process. In all cases, we observed an increase in the removal of the hormone with increasing contact time. By increasing the concentration of HS, there was an increase in the complexation of estrogens E2, and EE2 being that the hormone was EE2 that showed the best results of complexation with HS in the studied conditions. In aliquot removed from the system after 48 hours of stirring, was removed 51.1% (10.22 μg mL-1) in the presence of 10.0 μg mL-1 of the HS and 75.8% (15 16 μg mL-1) at 20 μg mL-1. The simulations can predict the behavior of E2 and EE2 hormones in natural aquatic environments rich in HS, where this interaction can reduce the availability to the biota and thus the absorption and physiological effects.